CLASSIFICATION OF THE HADRONIC DECAYS OF THE Z0 INTO B-QUARK AND C-QUARK PAIRS USING A NEURAL NETWORK - Abreu, P; Adam, W; Adye, T; Agasi, E; Alekseev, G; Algeri, A; Allen, P; Almehed, S; Alvsvaag, S; Amaldi, U; Anassontzis, E; Andreazza, A; et al. (1992)
A classifier based on a feed-forward neural network has been used for separating a sample of about 123 500 selected hadronic decays of the Z0, collected by DELPHI during 1991, into three classes according to the flavour of the original quark pair: uu+dd+ss (unresolved), cc and bb. The classification has been used to compute the partial widths of the Z0 into b and c quark pairs. This gave Γcc/Γh = 0.151 ± 0.008 (stat.) ± 0.041 (syst.), Γbb/Γh = 0.232±0.005 (stat.)±0.017 (syst.). © 1992.